Y-junction nanostructures of palladium: enhanced electrocatalytic properties for fuel cell reactions - Subhramannia, Mahima; Ramaiyan, Kannan; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of Electroanalytical Chemistry, 2009)
Here we demonstrate the utility of hierarchically designed alumina templates for the formation of palladium Y-junction nanostructures through a chemical vapor deposition route. These structures exhibit enhanced electrocatalytic activity for the oxidation of formic acid (up to 1020%) compared to that of platinum Y-junction nanostructures, which could be of immense relevance to portable fuel cell technology, since designing a better electrocatalyst for fuel cell reactions continues to be an important challenge. Apart from the obvious applications in fuel cell electrocatalysis, these Y-junction nanostructures could also act as promising candidates for room temperature hydrogen separation and more importantly as interconnects in molecular scale electronic devices. The present method of fabrication of Y-junction nanostructures using hierarchical alumina templates could be extended to other metallic/semiconducting systems facilitating more general opportunities for such hierarchical designs in nanoelectronics. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: electrocatalysts; fuel cells; Hierarchical structures; Nanostructure; Porous alumina membrane; Y-junctions